1999
DOI: 10.1074/jbc.274.17.12115
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between the Aryl Hydrocarbon Receptor and Hypoxia Inducible Factor Signaling Pathways

Abstract: The aryl hydrocarbon receptor (AHR) and the ␣-class hypoxia inducible factors (HIF1␣, HIF2␣, and HIF3␣) are basic helix-loop-helix PAS (bHLH-PAS) proteins that heterodimerize with ARNT. In response to 2,3,7,8-tetrachlorodibenzo-p-dioxin, the AHR⅐ARNT complex binds to "dioxin responsive enhancers" (DREs) and activates genes involved in the metabolism of xenobiotics, e.g. cytochrome P4501A1 (Cyp1a1). The HIF1␣⅐ARNT complex binds to "hypoxia responsive enhancers" and activates the transcription of genes that regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(144 citation statements)
references
References 32 publications
7
134
2
1
Order By: Relevance
“…Hypoxia also induces proteasomedependent degradation of ERα resulting in decreased E2-responsiveness ; however, we also observed that inhibitory AhR-ERα crosstalk was significantly decreased in breast cancer cells grown under hypoxic conditions (Stoner, 2002), and this is consistent with other reports showing that hypoxia decreases Ah-responsiveness (Chan et al, 1999;Gradin et al, 1996;Kim et al, 2000;Pollenz et al, 1999;Prasch et al, 2004). However, the mechanisms of hypoxia-dependent loss of Ah-responsiveness are unclear.…”
Section: Introductionsupporting
confidence: 92%
See 4 more Smart Citations
“…Hypoxia also induces proteasomedependent degradation of ERα resulting in decreased E2-responsiveness ; however, we also observed that inhibitory AhR-ERα crosstalk was significantly decreased in breast cancer cells grown under hypoxic conditions (Stoner, 2002), and this is consistent with other reports showing that hypoxia decreases Ah-responsiveness (Chan et al, 1999;Gradin et al, 1996;Kim et al, 2000;Pollenz et al, 1999;Prasch et al, 2004). However, the mechanisms of hypoxia-dependent loss of Ah-responsiveness are unclear.…”
Section: Introductionsupporting
confidence: 92%
“…It has previously been suggested that HIF-1α or other proteins that competitively displace the AhR from binding Arnt may that decrease Ah-responsiveness in cells grown under hypoxia (Chan, Yao, Gu, and Bradfield, 1999;Gradin, McGuire, Wenger, Kvietikova, fhitelaw, Toftgard, Tora, Gassmann, and Poellinger, 1996;Kim and Sheen, 2000;Pollenz, Davarinos, and Shearer, 1999;Prasch, Andreasen, Peterson, and Heideman, 2004). However, we show that overexpression of Arnt in transfection assays (Fig.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations